Microstructure test method for metal filament, thin strip or coating
By using a focused ion beam scanning electron microscope in the vacuum chamber, microstructure tests of metal filaments, thin strips or platings, the problems of complex sample preparation and difficult grain boundary observation in traditional methods are solved, and efficient and accurate microstructure is achieved Structural detection.
Patent Information
- Application Number
- CN202411656787.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-19
AI Technical Summary
The prior art is difficult to effectively carry out microstructure tests of metal filaments, thin strips or platings, especially when the sample size is small, the purity is high and the corrosion resistance is strong. Traditional metallographic sample preparation methods include resin embedding and mechanical. The limitations of grinding and corrosion operations lead to difficulties in grain boundary observation and false images.
Microstructure tests are performed in the vacuum chamber by using a focused ion beam scanning electron microscope. By adjusting the parameters such as ion beam acceleration voltage, beam current, scanning speed and contrast, the ion beam vertical incident and focus are achieved, and materials in the nano-level depth area of the surface layer are synchronized. Uniform removal and acquisition of grain orientation information.
Without the need for traditional metallographic samples to embed resin and mechanical polishing, sample preparation and microstructure display are completed directly in the vacuum chamber. It is simple to operate and efficient, avoiding the use of corrosive chemicals and contact with high-speed rotating equipment, which is significantly Improve the detection accuracy of microstructure structure.
Smart Images

Figure CN119470528A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of material physical and chemical property detection, in particular to a microstructure test method for metal filaments, thin strips or coatings. Background Art
[0002] In the field of microelectronics, metal bonding wires and connecting pieces with diameters or thicknesses of several hundred or even tens of microns are often used to achieve electrical connections or signal transmission, and gold or nickel plating of one to more than ten microns is usually required for surface conductivity and corrosion protection of the packaging structure. The quality of the above-mentioned bonding wires, connecting pieces, and platings directly affects the service life and service reliability of microelectronic components and subassemblies. In order to verify whether the performance of bonding wires, connecting pieces, and platings can meet the requirements of use, verification tests need to be carried out on them. Usually, verification tests need to include chemical composition, mechanical properties (including plating bonding strength), organizational structure, and environmental adaptability (resistance to salt spray, damp heat, etc.).
[0003] For samples with diameters or thicknesses ranging from a few microns to several hundred microns, energy spectrometers, spectrometers, electron probes, X-ray photoelectron spectrometers, Auger electron spectrometers and other instruments and equipment can be used for testing in the field of chemical composition; microhardness testers, nanoindenters, nanoscratch testers and other instruments and equipment can be used for testing in the field of mechanical properties; and salt spray test chambers, wet heat test chambers and other simulated service environments can be used in the field of environmental adaptability, and then stereo microscopes, scanning electron microscopes and other instruments and equipment can be used to analyze the surface corrosion and damage marks of samples after environmental tests. However, the field of organizational structure, especially the field of microstructure, is still limited by the small size of samples, which makes it impossible to implement conventional metallographic sample preparation operations such as resin embedding + mechanical grinding and polishing, and the high purity and strong corrosion resistance of samples (such as pure gold bonding wires and coatings, pure aluminum bonding wires, etc.). Chemical etching solutions or electrolytic etching solutions are difficult to display grain boundaries or will produce more pitting pits or false images that affect observation, resulting in the lack of effective microstructure test methods for bonding wires, connecting sheets, and coating materials. If microstructure testing cannot be carried out in the production, research and development, and failure analysis of bonding wires, connecting sheets, and coatings, it will be impossible to explain changes in macroscopic performance from the level of the essential characteristics of the material's microstructure, which is not conducive to product improvement and the upgrading of production technology levels. The relevant fields are in urgent need of finding a convenient, fast, and effective microstructure testing method. Summary of the invention
[0004] The present invention provides a microstructure test method for metal filaments, thin strips or coatings, with the purpose of intuitively, quickly and accurately obtaining microstructure information of metal filaments, thin strips and coatings that is difficult to obtain by traditional metallographic corrosion methods, solving the problem of detecting the microstructure of materials and material products such as bonding wires, connecting sheets, coatings, etc. commonly used in the field of microelectronics, and filling the gap in test methods.
[0005] In a first aspect, a microstructure test method for a metal filament, a thin strip or a coating is provided, comprising:
[0006] Place the sample in the vacuum chamber, adjust the position of the test surface to make it perpendicular to the incident direction of the ion beam, and adjust the distance between the test surface and the ion beam generator so that the ion beam can be focused on the test surface;
[0007] Set the ion beam acceleration voltage, the first magnification, and the first beam current; set the first scanning speed for continuous scanning, focus, and adjust the contrast and brightness until the image is clear;
[0008] Positioning near the area to be observed on the test surface, based on the first magnification and the first beam current, the first beam current is changed to the second beam current, and the second beam current satisfies that, under the expected magnification, after focusing and adjusting the contrast and brightness, the image contrast of the grain orientation can be obtained after scanning within N times, wherein the first magnification is less than the expected magnification;
[0009] Set the first magnification and the first beam current, focus and adjust the contrast and brightness until the image is clear, locate the area to be observed, zoom in to the expected magnification, shield the beam current and pause scanning;
[0010] Set the ion beam acceleration voltage, second beam current, first scanning speed, contrast and brightness, release the beam shielding and start scanning. After the image scan completes N scans, set the scanning speed to the second scanning speed, and then perform M scans to obtain a clear image, where N>M, and the second scanning speed is slower than the first scanning speed.
[0011] In conjunction with the first aspect, in some implementations of the first aspect, the method satisfies at least one of the following:
[0012] The first beam current is less than 80pA;
[0013] The second beam current is 80pA to 0.23nA;
[0014] The first scanning speed or the second scanning speed is 100 ns to 30 μs;
[0015] N is 5 to 25;
[0016] M is 1 to 5.
[0017] In conjunction with the first aspect, in some implementations of the first aspect, the method satisfies at least one of the following:
[0018] The first beam current intensity is 1pA to 65nA;
[0019] The first scanning speed is 200ns to 500ns;
[0020] The first scanning speed is 3 μs to 30 μs.
[0021] In combination with the first aspect, in certain implementations of the first aspect, the first beam current used for a sample less than 1 μm thick is 1 pA to 40 pA.
[0022] In combination with the first aspect, in some implementations of the first aspect, based on the first magnification factor and the first beam current, converting the first beam current to the second beam current includes:
[0023] Based on the first magnification, the magnification is gradually increased to a second magnification, and the second magnification satisfies that the image contrast of the grain orientation can be obtained after N scans after focusing, adjusting the contrast and brightness, and the second magnification at this time is recorded as Z;
[0024] If Z is lower than the expected magnification, the beam current is reduced based on the first beam current, and the adjusted second beam current satisfies that when the magnification is reached to the expected magnification, the image contrast of the grain orientation can be obtained after N scans within the range after focusing, adjusting the contrast and brightness;
[0025] If Z is not lower than the expected magnification, it is adjusted to the expected magnification. If the image contrast of the grain orientation can be obtained after N scans after focusing and adjusting the contrast and brightness, the beam adjustment is not performed based on the first beam current used. If the image contrast of the grain orientation cannot be obtained after N scans after focusing and adjusting the contrast and brightness, the beam current is increased based on the first beam current, and the adjusted second beam current satisfies that, at the expected magnification, the image contrast of the grain orientation can be obtained after N scans after focusing and adjusting the contrast and brightness.
[0026] In combination with the first aspect, in some implementations of the first aspect, the first magnification is 60 times to 1000 times.
[0027] In combination with the first aspect, in some implementations of the first aspect, the method further includes:
[0028] The test surface is pretreated to obtain a smooth surface with a roughness equal to or better than Ra0.2 and no organic pollutants attached to the observed area. The pretreatment includes at least one of the following: wire cutting, mechanical cutting, mechanical grinding, vibration polishing, chemical polishing, electrolytic polishing, solvent cleaning, and ion beam cutting.
[0029] In conjunction with the first aspect, in certain implementations of the first aspect, the preprocessing of the test surface satisfies at least one of the following:
[0030] When the test surface is a cross section of a metal filament, ion beam cutting is used to prepare the cross section;
[0031] When the test surface is a cross section in the thickness direction of the thin strip, a scalpel is used to cut to obtain the cross section, and ion beam cutting is used to trim the mechanically cut edge based on the cut surface;
[0032] When the test surface is a cross section in the coating thickness direction, the cross section is cut out by wire cutting, and then mechanical grinding, mechanical polishing and / or vibration polishing are performed, and then ion beam cutting is used to trim the polished surface;
[0033] Cold-drawn wires, cold-rolled strips or original surfaces of coatings that have not been mechanically processed can be used directly for testing after solvent cleaning.
[0034] In combination with the first aspect, in some implementations of the first aspect, after determining the value of the second beam current, the method further includes:
[0035] Based on the ion beam acceleration voltage, the second beam current, the first scanning speed, the contrast and the brightness, all relevant parameters are recorded;
[0036] Keep the magnification constant and move to the adjacent area to verify whether the parameter settings are appropriate.
[0037] In conjunction with the first aspect, in some implementations of the first aspect, the method satisfies at least one of the following:
[0038] The vacuum environment of the vacuum chamber is equal to or better than 7×10 -3 Pa;
[0039] The ion beam acceleration voltage is 5 kV to 30 kV.
[0040] Compared with the prior art, the solution provided by the present invention includes at least the following beneficial technical effects:
[0041] (1) The present invention can obtain the microstructure of metal bonding wires, connecting sheets and coatings with a diameter or thickness of several hundred or even more than ten microns without the traditional metallographic sample preparation process of resin embedding + mechanical grinding and polishing, and corrosion. After the sample is simply pretreated (mainly solvent cleaning), the remaining sample preparation and microstructure display work can be completed synchronously in the vacuum chamber of the focused ion beam scanning electron microscope equipment. The operation is simple and efficient, and no corrosive chemicals are required, and no high-speed rotating equipment (such as mechanical grinding and polishing equipment) is required. It solves the problems that small-sized samples with micron scale (diameter or thickness) are difficult to operate, high-purity samples have good corrosion resistance and are not easily corroded (chemical corrosion or electrolytic corrosion), and pitting pits or false images that affect observation are easily generated during metallographic sample preparation. It is particularly suitable for microstructure testing of bonding wires, connecting sheets, and coating materials widely used in the field of microelectronics, and can solve the problem that the above materials have long lacked effective microstructure testing methods.
[0042] (2) Different from the conventional ion beam cutting and ion beam imaging methods, in the microstructure test process of the present invention, the ion beam is incident perpendicularly to the surface of the sample to be tested. The ion beam scans the sample surface under the applicable and controlled ion beam incident direction, ion beam acceleration voltage, ion beam current, scanning time, number of scans, contrast and contrast adjustment, and focus adjustment combination parameters obtained through preliminary experiments, thereby achieving uniform removal of materials in the nanometer-scale depth region of the surface layer and simultaneously utilizing the characteristics that the ion stripping effect and the intensity of the secondary electron signal excited by ions are affected by the different crystal plane orientations of the polycrystalline metal material to obtain an image containing the contrast of the crystal orientation information, thereby obtaining the microstructure information of the sample test surface.
[0043] (3) Unlike the existing ion etching technology that can only remove materials, although the method described in the present invention also uses an ion beam, the ion beam etching amount is relatively small and concentrated in the area of interest, and the ion stripping depth is nanometer-level and relatively uniform, which can avoid the formation of hole defects or embossing effects due to the difference in etching properties of local defects of the material. In addition, the present invention can be observed in situ in the vacuum chamber, which can avoid oxidation and contamination during sample processing and transfer, and can directly perform microstructure imaging observation on the area of interest. Ion etching technology can be used as a pretreatment method when the surface roughness of the sample does not meet the requirements of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 This is the ion beam imaging of copper foil (the middle is the microstructure test area).
[0045] Figure 2 Electron beam imaging of copper foil (the middle is the microstructure test area).
[0046] Figure 3 It is the boundary between the copper foil microstructure test area and the surrounding samples (nanoscale-depth peeling of the surface layer of the test area).
[0047] Figure 4 This is the cross-sectional microstructure of the aluminum-silicon bonding wire.
[0048] Figure 5 This is the morphology of the aluminum-silicon bonding wire after ion etching.
[0049] Figure 6 This is the microstructure of the surface sample of the electrolytic copper foil (10μm thick) connecting piece.
[0050] Figure 7 This is the microstructure of the cross-section sample of the electrolytic copper foil (10μm thick) connecting piece.
[0051] Figure 8 This is the microstructure of the surface sample of the aluminum-plated polyester film (the thickness of the aluminum coating is less than 1μm).
[0052] Fig. 9This is the microstructure of the surface sample of the gold-plated layer (thickness 1.5μm) of the plastic-sealed device shell. DETAILED DESCRIPTION
[0053] The present invention is further described in detail below with reference to the accompanying drawings and specific embodiments.
[0054] refer to Figures 1 to 3 The present invention provides a microstructure testing method for metal filaments, thin strips or coatings, and the specific steps are as follows.
[0055] Step (1), check whether the sample test surface is smooth (roughness and cleanliness).
[0056] If the test surface is too rough or there are contaminants covering the area to be tested, wire cutting and / or mechanical cutting and / or mechanical grinding and polishing and / or vibration polishing and / or chemical polishing and / or electrolytic polishing and / or solvent cleaning and / or ion beam cutting are required to obtain a smooth surface with a roughness equal to or better than Ra0.2 and no organic contaminants attached to the area to be observed.
[0057] In some embodiments, when the test surface is a cross section of a metal filament (with a diameter of less than 200 μm), ion beam cutting may be used to prepare the cross section.
[0058] In some embodiments, when the test surface is a cross-section in the thickness direction of a thin strip (thickness less than 200 μm), a mechanical cutting method such as a scalpel cutting can be used to obtain the cross-section. If necessary, ion beam cutting can be used to trim the mechanically cut edges based on the cut surface to remove local plastic deformation areas caused by mechanical cutting.
[0059] In some embodiments, when the test surface is a cross-section in the coating thickness direction (thickness less than 200 μm), wire cutting can be used to cut the cross-section, followed by mechanical grinding, and if necessary, mechanical polishing and (or) vibration polishing, and then ion beam cutting can be used to trim the polished surface to remove local plastic deformation areas caused by polishing.
[0060] In some embodiments, the raw surface of cold-drawn wire, cold-rolled strip or coating without mechanical processing can be directly used for testing after being cleaned with solvent.
[0061] According to the experience summarized by the applicant during the research process, the oxide layer, deformation layer or contamination layer on the sample surface will cause the ion beam to not evenly strip metal atoms when stripping to the underlying substrate, which will lead to the inability to obtain grain orientation information locally or produce false images due to uneven stripping. The surface state of the sample needs to be checked before testing, and pretreatment should be performed if necessary.
[0062] Step (2), placing the sample in a vacuum chamber, adjusting the position of the test surface so that it is perpendicular to the incident direction of the ion beam, and adjusting the distance between the test surface and the ion beam generator so that the ion beam can be focused on the test surface.
[0063] The working principle of the focused ion beam scanning electron microscope is similar to that of the scanning electron microscope. The difference between the two is that the focused ion beam scanning electron microscope uses ions (such as gallium, helium, etc.) while the scanning electron microscope uses electrons. The focused ion beam scanning electron microscope is more inclined to perform surface micro-nanoscale processing (cutting, deposition), while the scanning electron microscope can only perform surface imaging.
[0064] The sample test surface is perpendicular to the ion beam incident direction so that the sample can be uniformly eroded (stripped) during the ion beam scanning process, thereby laying the foundation for displaying the grain orientation contrast. In some embodiments, the vacuum chamber of the focused particle beam scanning electron microscope is used to achieve an equivalent or better than 7×10 -3 Pa vacuum environment, too low vacuum will affect the ion beam intensity and focusing effect.
[0065] Step (3), setting the ion beam acceleration voltage, the first magnification, the first beam current; setting the first scanning speed for continuous scanning, focusing and adjusting the contrast and brightness until the image is clear. This step is used to reduce sample surface damage.
[0066] In some embodiments, the ion beam acceleration voltage is 5 kV to 30 kV. This is to adapt to samples of different thicknesses. The ion stripping effect is weaker under lower electric field strengths, which can protect the sample and can be used to initially locate the test position. Under higher electric field strengths, the ion stripping effect is enhanced and the depth and intensity of the excited secondary electron signal increase, which is conducive to obtaining the orientation information of the sample substrate without being affected by the surface roughness.
[0067] In some embodiments, the first magnification is 60 times to 1000 times.
[0068] In some embodiments, the first beam current does not exceed 80pA. The first beam current intensity obtained after the ion beam is accelerated by the electric field can be adjustable from 1pA to 65nA. Samples less than 1μm thick should use a smaller beam current, such as 1pA to 40pA. The ion stripping effect of a smaller beam current intensity is weaker, which can protect the sample and can be used to preliminarily locate the test position. The ion stripping effect of a larger beam current intensity is enhanced and the intensity of the excited secondary electron signal is increased, which is beneficial to improving the signal-to-noise ratio of obtaining the orientation information of the sample substrate, but too high a beam current intensity will reduce the resolution of the image.
[0069] In some embodiments, the ion source of the ion beam is, for example, gallium (Ga) ions.
[0070] In some embodiments, the resolution of the focused image can be equal to or better than 5 nm, so as to ensure that the image obtained by scanning line by line and frame by frame can have a nanometer-level spatial resolution.
[0071] In some embodiments, the first scanning speed is 100 ns to 30 μs. Further, the first scanning speed is a medium to fast scanning speed, ranging from 200 ns to 500 ns.
[0072] Step (4), positioning near the area to be observed on the test surface. Based on the first magnification in step (3), gradually increase the magnification to a second magnification, the second magnification being sufficient to obtain the image contrast of the grain orientation after N scans after focusing, adjusting the contrast and brightness, and recording the second magnification at this time as Z, where N is 1 time (or 1 frame, each frame consisting of multiple reciprocating scan lines) or more.
[0073] If Z is lower than the expected magnification (under the expected magnification, the area to be observed is fully displayed and the area percentage of the image exceeds the preset area percentage), the beam current is reduced based on the first beam current used in step (3), and the adjusted second beam current satisfies that when it is magnified to the expected magnification, the image contrast of the grain orientation can be obtained after focusing and adjusting the contrast and brightness within N scans.
[0074] If Z is not lower than the expected magnification, it is adjusted to the expected magnification. If the image contrast of the grain orientation can be obtained after N scans after focusing and adjusting the contrast and brightness, the beam adjustment is not performed based on the first beam used in step (3). If the image contrast of the grain orientation cannot be obtained after 20 consecutive scans after focusing and adjusting the contrast and brightness, the beam is increased based on the first beam used in step (3). The adjusted second beam satisfies that, at the expected magnification, the image contrast of the grain orientation can be obtained after N scans after focusing and adjusting the contrast and brightness.
[0075] This step is a preliminary experiment to obtain the final specific parameters in order to quickly obtain the optimal combination parameters suitable for the sample.
[0076] In some embodiments, N scans are 5 to 20 consecutive scans.
[0077] In some embodiments, the recommended second beam current for imaging is 80 pA to 0.23 nA (which can ensure 15,000 times clearer images).
[0078] Step (5) records all relevant parameters based on the ion beam acceleration voltage, beam current, scanning speed, contrast and brightness obtained in step (4). If necessary, the magnification can be kept unchanged and moved to the adjacent area to verify whether the parameter settings are appropriate. This step is to verify the combined parameters obtained in step (4) to ensure that the formal test can obtain satisfactory results.
[0079] Step (6), set to the first magnification and the first beam in step (3) again, focus and adjust the contrast and brightness until the image is clear, locate the area to be observed, zoom in to the expected magnification, shield the beam and pause scanning. This step is used to locate the test area.
[0080] Step (7), setting the ion beam acceleration voltage, beam current, scanning speed, contrast and brightness to the parameters recorded in step (5). This step is used to set the parameter combination verified in (5).
[0081] Step (8), remove the beam shielding and start scanning. After the image scanning is completed N times, the scanning speed is set to the second scanning speed, and then M scans are performed to obtain a clear image (microstructure).
[0082] During the scanning process, the ion beam focused into a point has been scanning the sample surface line by line and back and forth. The first scanning speed of medium to fast and multiple scannings at the beginning are to ensure that the ion beam can react with the sample surface as evenly and consistently as possible. If the scanning speed is slow, the material will be damaged after the ion beam and the sample surface are in contact for a long time, and uneven pits in strips or local points may be produced. When imaging, using a medium to slow second scanning speed is conducive to obtaining a clear image. If a fast scan is used when imaging, the image will not be clear.
[0083] If necessary, focus again and adjust the contrast and brightness. If some samples, especially those with a thickness of less than 1μm, are scanned too many times, the test results may be affected. At this time, the operation should be performed as soon as possible to minimize the total number of scans. This step is a formal test of the sample test surface. By using the verified combination parameters to simultaneously achieve the purpose of surface ion stripping and grain orientation display, a contrast image containing the sample microstructure morphology information is obtained. The ion beam produces a stripping effect on the atoms of the nanometer-level thickness on the surface of the sample test surface, while exciting the secondary electron signal. The stripping effect and the excitation intensity of the secondary electron signal are affected by the different crystal plane orientations of the polycrystalline metal material to obtain an image containing the crystal orientation information contrast, and then obtain the microstructure information of the sample test surface. Image contrast is used to display microstructure information, including: grain boundaries, twin boundaries, grain size and shape, differences in different grain orientations, inclusions and other material defect distributions.
[0084] In some embodiments, the second scanning speed is 100 ns to 30 μs. Further, the second scanning speed is a medium to slow scanning speed, ranging from 3 μs to 30 μs.
[0085] In some embodiments, M scans are 1 to 5 scans.
[0086] Step (9), if necessary, repeat (2) to (8) to obtain microstructure information of other areas or magnifications of the sample test surface.
[0087] Step (10): If other samples need to be tested, repeat steps (1) to (9).
[0088] When the ion beam acts on the sample surface, it will stimulate secondary electron signals and secondary ion signals. Image information can be obtained by collecting secondary electron signals and performing signal processing. The present invention uses a specific combination of parameters, including ion beam incident direction, ion beam acceleration voltage, ion beam current, scanning time, number of scans, contrast and contrast adjustment, focus adjustment, and sample initial surface state processing. During the process of continuous ion beam scanning of the sample surface, the present invention can simultaneously achieve uniform removal of materials in the shallow surface nanometer-level depth area and simultaneously utilize the characteristics that the ion stripping effect and the ion-excited secondary electron signal intensity are affected by the different crystal plane orientations of polycrystalline metal materials to obtain an image containing crystal orientation information contrast, thereby obtaining microstructure information of the sample test surface.
[0089] The present invention provides a microstructure test method, wherein an ion beam (5) having a specific beam current intensity (4) is used to scan (9) a pre-treated sample test surface (8) at a specific scanning speed (6) and a scanning number (7) under a high vacuum test environment (1), generate image contrast (10), and then obtain microstructure information (11) of the sample test surface.
[0090] (1) Using the vacuum chamber of a focused particle beam scanning electron microscope to achieve a performance equal to or better than 7×10 -3 Pa vacuum environment, too low vacuum will affect the ion beam intensity and focusing effect.
[0091] (2) The resolution of the image after focusing can be equal to or better than 5 nm, so as to ensure that the image obtained by scanning line by line and frame by frame can have a nanometer-level spatial resolution.
[0092] (3) The ion acceleration electric field strength (ion beam acceleration voltage) is adjustable from 5kV to 30kV. To adapt to samples of different thicknesses, the ion stripping effect is weaker at lower electric field strengths, which can protect the sample and can be used to initially locate the test position. At higher electric field strengths, the ion stripping effect is enhanced and the depth and intensity of the excited secondary electron signal increase, which is conducive to obtaining the orientation information of the sample substrate without being affected by the surface roughness.
[0093] (4) After the ion beam is accelerated by the electric field described in (2), the beam intensity is adjustable from 1pA to 65nA. The ion stripping effect of a smaller beam intensity is weaker, which can protect the sample and can be used to initially locate the test position. The ion stripping effect is enhanced with a larger beam intensity and the intensity of the excited secondary electron signal is increased, which is beneficial to improving the signal-to-noise ratio of the orientation information of the sample substrate, but too high a beam intensity will reduce the resolution of the image. The recommended imaging beam current verified by experiments is 80pA to 0.23nA (which can ensure a 15,000-fold clear image).
[0094] (5) Gallium (Ga) ions: This is a common and easily available ion source.
[0095] (6) The scanning time for each line is 100ns to 30μs. If the scanning time is short, the stripping effect of the ions is weak, which can protect the sample and can be used to initially locate the test position, but the image resolution is poor. If the scanning time is long, the stripping effect of the ions is strong and the excited signal is strong, which is beneficial to improve the signal-to-noise ratio of the orientation information of the sample substrate. However, too high a scanning time will cause differences in the degree of stripping of each line scan, affecting the uniform contrast of the image. The recommended commonly used scanning speeds are 300ns (fast), 500ns (medium), and 10μs (slow).
[0096] (7) More than 1 scan (or 1 frame, each frame consists of multiple reciprocating scan lines), 5 to 20 scans are recommended. If the number of scans is too small, the surface oxide layer, deformation layer or contamination layer will not be removed sufficiently and the crystal orientation information cannot be obtained. If the scan time is too long, relief will be generated due to the difference in the ablation rate of different orientations, and even false images will be generated due to ion implantation.
[0097] (8) The smooth surface obtained in the original state and / or after wire cutting and / or mechanical cutting and / or mechanical grinding and polishing and / or chemical polishing and / or electrolytic polishing and / or vibration polishing and / or solvent cleaning and / or ion beam cutting. If there is an excessively thick oxide layer, deformation layer or contamination layer on the surface, the ion beam cannot evenly strip metal atoms when stripping to the underlying substrate, which in turn leads to the inability to obtain grain orientation information locally or to the generation of false images due to uneven stripping.
[0098] (9) The ion beam complies with the settings in (2), (3), and (4) and the incident direction is perpendicular to the test surface for line-by-line reciprocating scanning. The scanning parameters comply with the settings in (6), and (7).
[0099] (10) The ion beam produces a stripping effect on the atoms of the nanometer-level thickness on the surface of the sample test surface and simultaneously stimulates the secondary electron signal. The principle that both the stripping effect and the excitation intensity of the secondary electron signal are affected by the different crystal plane orientations of the polycrystalline metal material is used to obtain a contrast image containing crystal orientation information, thereby obtaining the microstructural information of the sample test surface.
[0100] This principle is different from traditional ion beam cutting which only focuses on material removal. Traditional ion beam cutting generally uses a larger beam current such as 40nA to 65nA for rough cutting, and then uses a medium beam current such as 0.23nA to 2.5nA for trimming. The test surface is perpendicular to the direction of the ion beam, and the ion beam only serves to strip the material to remove the material. Although it is also scanned line by line during cutting, the beam current is very large and the cutting depth is very large, resulting in uneven ion stripping between different scanning lines. The surface roughness after stripping is very large, and the contrast formed by the grain orientation of the ion beam is completely masked by the roughness and cannot be obtained.
[0101] This principle is different from traditional ion beam imaging. Traditional ion beam imaging often uses a smaller beam current such as 4pA to 80pA to minimize the effect of ion stripping on the sample surface so as to observe the original morphological information of the sample surface. The observation of sample surface information more generally uses an electron beam with lower energy as the incident source. Ion beam imaging is usually only used for auxiliary positioning before ion beam cutting.
[0102] After pre-treating the sample to obtain a clean surface with a temperature not exceeding Ra0.2, the present invention uses a specific combination of parameters, including ion beam incident direction, ion beam acceleration voltage, ion beam current, scanning time, number of scans, contrast and contrast adjustment, and focus adjustment. During the continuous scanning of the sample surface by the ion beam, the material in the shallow surface nanometer-level depth region can be uniformly removed, and an image containing crystal orientation information contrast can be obtained by utilizing the characteristics that both the ion stripping effect and the ion-excited secondary electron signal intensity are affected by the different crystal plane orientations of the polycrystalline metal material, thereby obtaining the microstructure information of the sample test surface.
[0103] (11) Use the image contrast of (10) to display microstructural information, including grain boundaries, twin boundaries, grain size and shape, orientation differences of different grains, inclusions and other material defect distributions.
[0104] Example 1: Microstructure of cross section of aluminum-silicon bonding wire
[0105] (1) After inspection, the sample can be used directly for testing. A bonding wire sample with a length of about 10 mm is cut and cut into a cross-section sample using a focused particle beam.
[0106] (2) The bonding wire cross-section sample obtained in (1) is placed in a vacuum chamber and the cross-section is adjusted to be perpendicular to the ion beam incident direction.
[0107] (3) Based on the experience accumulated from previous experiments, the ion beam acceleration voltage was set to 30 kV, the magnification was set to 3000 times to cover the entire cross-section of the bonding wire, the beam current was set to 80 pA, the scanning speed was set to 200 ns for continuous scanning, and the focus was adjusted and the contrast and brightness were adjusted until the image was clear.
[0108] (4) Position the image center so that it is roughly aligned with the center of the gold bonding wire cross section. Adjust the magnification to 3965 times so that the image covers the entire cross section. Shield the beam, set the beam current to 2.5 nA, and set the scan speed to 10 μs.
[0109] (5) Remove the beam shielding, adjust the contrast and brightness, and scan five times in a row to obtain a clear image of the microstructure (see Figure 4 ).
[0110] Samples treated with ion etching technology (see Figure 5 ), the method of the present invention can clearly display the grains, while the sample processed by ion etching technology only shows the cross section with more pits, and cannot display the grain information. The reason may be that the etching causes the area with poor corrosion resistance to be over-etched and the sample is oxidized by air after etching. It also verifies that the present invention has significant advantages over the etching technology that also uses ion beams.
[0111] Example 2: Microstructure of the electrolytic copper foil (10 μm thick) connecting piece
[0112] (1) After inspection, the sample was cleaned with anhydrous ethanol for 5 minutes and dried before use in the test. A thickness section specimen (about 5 mm in height and 7 mm in length) was prepared by scalpel cutting, and a surface specimen of about 10 mm × 8 mm was cut by scissors.
[0113] (2) Place the cross-section sample and the surface sample described in (1) in a vacuum chamber. Adjust the position of the surface sample so that it is perpendicular to the incident direction of the ion beam, and adjust the distance between the test surface and the ion beam generator so that the ion beam can be focused on the test surface.
[0114] (3) Set the ion beam acceleration voltage to 30 kV, the magnification to 100 times, the beam current to 80 pA, the scanning speed to 200 ns continuous scanning, focus, and adjust the contrast and brightness until the image is clear.
[0115] (4) Position the camera near the area to be observed on the test surface. Based on the magnification in (3), gradually increase the magnification until the image contrast of the grain orientation can be obtained within 5 to 20 times after focusing, contrast and brightness are adjusted. The magnification at this time is recorded as 15,000 times.
[0116] Because the expected magnification is 6500 times, which is lower than 15000 times, the magnification is adjusted to 6500 times. After focusing and adjusting the contrast and brightness, the image contrast of the grain orientation cannot be obtained after 20 consecutive scans. Then, based on (3), the beam current is increased to 0.23nA. After focusing and adjusting the contrast and brightness, the image contrast of the grain orientation can be obtained after 15 consecutive scans.
[0117] (5) Based on the ion beam acceleration voltage, beam current, scanning speed, contrast and brightness obtained in (4) to obtain satisfactory grain orientation image contrast within 15 consecutive scans, record all relevant parameters. Keep the magnification unchanged and move to the adjacent area to verify that the parameter settings are appropriate and satisfactory results can be reproduced.
[0118] (6) Set to the lower magnification and smaller beam current in (3) again, focus and adjust contrast and brightness until the image is clear, locate the area to be observed, zoom in to the expected magnification, shield the beam and pause scanning.
[0119] (7) Set the ion beam acceleration voltage, beam current, scan speed, contrast, and brightness to the parameters recorded in (5): magnification 15,000 times, beam current 0.23 nA, ion beam acceleration voltage 30 kV, scan time 200 ns.
[0120] (8) Remove the beam shielding and start scanning. After the image scan is completed 15 times, set the scanning speed to 10 μs. Scan again once to obtain a clear image (see the surface sample microstructure for details). Figure 6 ).
[0121] (9) Repeat (2) to (8) to obtain a clear image of the cross-sectional sample, and change the expected magnification to 8000 times. It has been verified that the parameters in (7) are applicable. Therefore, after changing the new position, at a magnification of 8000 times, directly press (8) to complete the scanning imaging (see the cross-sectional sample microstructure). Figure 7 ).
[0122] Example 3: Microstructure of the coating surface sample of aluminized polyester film (aluminum coating thickness less than 1 μm)
[0123] (1) After inspection, the sample can be used directly. Use scissors to cut a piece of sample with a size of about 10mm×10mm.
[0124] (2) The sample is glued and fixed on the platform and placed in the vacuum chamber. The position of the test surface is adjusted so that it is perpendicular to the incident direction of the ion beam. The distance between the test surface and the ion beam generator is adjusted so that the ion beam can be focused on the test surface.
[0125] (3) Set the ion beam acceleration voltage to 5 kV, the magnification to 100 times, the beam current to 40 pA, the scanning speed to 300 ns continuous scanning, focus, and adjust the contrast and brightness until the image is clear.
[0126] (4) Position the camera near the area to be observed on the test surface. Based on the magnification in (3), gradually increase the magnification until the image contrast of the grain orientation can be obtained within 10 consecutive times after focusing, contrast and brightness are adjusted. The magnification at this time is recorded as 15,000 times.
[0127] Since 15,000 times is lower than the expected magnification of 30,000 times, the beam current is reduced to 24 pA based on the beam current used in (3), and the image is magnified to the expected magnification of 30,000 times. After focusing and adjusting the contrast and brightness, the image contrast of the grain orientation can be obtained after 5 consecutive scans.
[0128] (5) Based on the ion beam acceleration voltage, beam current, scanning speed, contrast and brightness obtained in (4) to obtain satisfactory grain orientation image contrast in 5 consecutive scans, all relevant parameters are recorded.
[0129] (6) Set the image to the lower magnification and smaller beam current in (3) again, focus and adjust the contrast and brightness until the image is clear, locate the area to be observed, shield the beam and pause scanning.
[0130] (7) Set the magnification to 30,000 times, the ion beam acceleration voltage to 30 kV, the beam current to 24 pA, the scan speed to 200 ns, and the contrast and brightness to the parameters recorded in (5).
[0131] (8) Remove the beam shield and start scanning. After the image is scanned once, set the scanning speed to 5 μs and scan again to obtain a clear image (see the microstructure for details). Figure 8 ).
[0132] Example 4: Microstructure of the surface sample of the gold-plated layer (thickness 1.5 μm) of the plastic-encapsulated device shell
[0133] (1) After inspection, the samples can be used directly.
[0134] (2) Place the sample in a vacuum chamber, adjust the position of the test surface so that it is perpendicular to the incident direction of the ion beam, and adjust the distance between the test surface and the ion beam generator so that the ion beam can be focused on the test surface.
[0135] (3) Set the ion beam acceleration voltage to 30 kV, the magnification to 200 times, the beam current to 80 pA, the scanning speed to 500 ns continuous scanning, focus, and adjust the contrast and brightness until the image is clear.
[0136] (4) Position the camera near the area to be observed on the test surface. Based on the magnification in (3), gradually increase the magnification until the image contrast of the grain orientation can be obtained after focusing, adjusting the contrast and brightness for 20 consecutive times. Record the magnification at this time as 12,500 times, which is basically consistent with the expected magnification. Record the parameters.
[0137] (5) Set to the lower magnification and smaller beam current in (3) again, focus and adjust contrast and brightness until the image is clear, locate the area to be observed, zoom in to the expected magnification, shield the beam and pause scanning.
[0138] (6) Set the ion beam acceleration voltage to 30 kV, beam current to 80 pA, scan speed to 500 ns, and contrast and brightness to the same parameters as (4).
[0139] (7) Remove the beam shield and start scanning. After completing 20 scans, set the scanning speed to 10 μs and scan again to obtain a clear image (see the surface sample microstructure for details). Fig. 9 ).
[0140] Although the present invention is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any person skilled in the art may make possible changes and modifications without departing from the spirit and scope of the present invention. Therefore, the scope of protection of the present invention shall be based on the scope defined by the claims of the present invention.
Claims
1. A method for testing the microstructure of metal filaments, thin strips or coatings, characterized in that: include: Place the sample in the vacuum chamber, adjust the position of the test surface to make it perpendicular to the incident direction of the ion beam, and adjust the distance between the test surface and the ion beam generator so that the ion beam can be focused on the test surface; Setting the ion beam acceleration voltage, the first magnification, and the first beam current; Set the first scanning speed to scan continuously, focus, and adjust the contrast and brightness until the image is clear; Positioning near the area to be observed on the test surface, based on the first magnification and the first beam current, the first beam current is changed to the second beam current, and the second beam current satisfies that, under the expected magnification, after focusing and adjusting the contrast and brightness, the image contrast of the grain orientation can be obtained after scanning within N times, wherein the first magnification is less than the expected magnification; Set the first magnification and the first beam current, focus and adjust the contrast and brightness until the image is clear, locate the area to be observed, zoom in to the expected magnification, shield the beam current and pause scanning; Set the ion beam acceleration voltage, second beam current, first scanning speed, contrast and brightness, release the beam shielding and start scanning. After the image scan completes N scans, set the scanning speed to the second scanning speed, and then perform M scans to obtain a clear image, where N>M, and the second scanning speed is slower than the first scanning speed.
2. The method according to claim 1, characterized in that The method satisfies at least one of the following: The first beam current is less than 80pA; The second beam current is 80pA to 0.23nA; The first scanning speed or the second scanning speed is 100 ns to 30 μs; N is 5 to 25; M is 1 to 5.
3. The method according to claim 2, characterized in that The method satisfies at least one of the following: The first beam current intensity is 1pA to 65nA; The first scanning speed is 200ns to 500ns; The first scanning speed is 3 μs to 30 μs.
4. The method according to claim 3, characterized in that: For samples less than 1 μm thick, the first beam current used is 1 pA to 40 pA.
5. The method according to claim 1, characterized in that The method of converting the first beam flow to a second beam flow based on the first magnification factor and the first beam flow comprises: Based on the first magnification, the magnification is gradually increased to a second magnification, and the second magnification satisfies that the image contrast of the grain orientation can be obtained after N scans after focusing, adjusting the contrast and brightness, and the second magnification at this time is recorded as Z; If Z is lower than the expected magnification, the beam current is reduced based on the first beam current, and the adjusted second beam current satisfies that when the magnification is reached to the expected magnification, the image contrast of the grain orientation can be obtained after N scans within the range after focusing, adjusting the contrast and brightness; If Z is not lower than the expected magnification, it is adjusted to the expected magnification. If the image contrast of the grain orientation can be obtained after N scans after focusing and adjusting the contrast and brightness, the beam adjustment is not performed based on the first beam current used. If the image contrast of the grain orientation cannot be obtained after N scans after focusing and adjusting the contrast and brightness, the beam current is increased based on the first beam current, and the adjusted second beam current satisfies that, at the expected magnification, the image contrast of the grain orientation can be obtained after N scans after focusing and adjusting the contrast and brightness.
6. The method according to claim 5, characterized in that The first magnification is 60 times to 1000 times.
7. The method according to claim 1, characterized in that The method further comprises: The test surface is pretreated to obtain a smooth surface with a roughness equal to or better than Ra0.2 and no organic pollutants attached to the observed area. The pretreatment includes at least one of the following: wire cutting, mechanical cutting, mechanical grinding, vibration polishing, chemical polishing, electrolytic polishing, solvent cleaning, and ion beam cutting.
8. The method according to claim 7, characterized in that The pre-processing of the test surface satisfies at least one of the following: When the test surface is a cross section of a metal filament, ion beam cutting is used to prepare the cross section; When the test surface is a cross section in the thickness direction of the thin strip, a scalpel is used to cut to obtain the cross section, and ion beam cutting is used to trim the mechanically cut edge based on the cut surface; When the test surface is a cross section in the coating thickness direction, the cross section is cut out by wire cutting, and then mechanical grinding, mechanical polishing and / or vibration polishing are performed, and then ion beam cutting is used to trim the polished surface; Cold-drawn wires, cold-rolled strips or original surfaces of coatings that have not been mechanically processed can be used directly for testing after solvent cleaning.
9. The method according to claim 1, characterized in that: After determining the value of the second beam current, the method further includes: Based on the ion beam acceleration voltage, the second beam current, the first scanning speed, the contrast and the brightness, all relevant parameters are recorded; Keep the magnification constant and move to the adjacent area to verify whether the parameter settings are appropriate.
10. The method according to claim 1, characterized in that The method satisfies at least one of the following: The vacuum environment of the vacuum chamber is equal to or better than 7×10 -3 Pa; The ion beam acceleration voltage is 5 kV to 30 kV.
Citation Information
Patent Citations
Method for positioning and detecting conductive path on surface of glass sealing structure
CN112461880A
Preparation method of pore surface ion channel contrast sample
CN112730006A
Reamed modified molecular sieve and preparation method thereof
CN116354361A
Microstructure displaying method of precious metal sample
CN118209575A
Sample cross-section observing method in fib-sem device and fib-sem device
JP1999213935A
Cited By
Three-dimensional scanning type secondary ion mass spectrometry method and device for semiconductor sample
CN122409731A